EDITORIAL: Pitfalls in Online Teaching & Examinations - Haque, Anwar Ul (International Journal of Pathology, 2021)
Someone had said that world will never be the same after corona virus; how true! Of course, we cannot comprehend “never” as no one knows the limit of this never! But for the conceivable near future, we may say that until corona pandemic is gone the world will not be the same. One big change with corona pandemic is institution of online teaching across the world; for all age groups and all types and all levels of students. No doubt online teaching and learning have several distinct advantages such as saving time and money on travel and home convenience etc. but it also has several disadvantages and limitations for students, teachers, parents, institutions and the society as a whole. These problems are worse for the underdeveloped and resource depleted countries.